Analysis of Clean Water Distribution Pipe Implementation Time Using Value Engineering Method in Rungkut Industri Surabaya - Ahmad Rois; Esti Wulandari; Jaka Purnama (Jurnal Teknik Indonesia, 2026)
Clean water distribution infrastructure projects in industrial areas face significant challenges related to cost efficiency and implementation time, which directly impact project sustainability and operational effectiveness. This study analyzes the cost and time efficiency of the clean water distribution system in the Rungkut industrial area, Surabaya, by applying the Value Engineering (VE) method. The main objective of this study is to evaluate and compare the performance of three commonly used types of pipes—namely HDPE (High-Density Polyethylene), uPVC (unplasticized polyvinyl chloride), and GI (galvanized iron)—to determine the most optimal alternative without reducing the function or quality of the clean water distribution system. Data collection was conducted through a combination of methods: distributing questionnaires to professional respondents in civil engineering and water installation fields, conducting direct interviews with project-related parties, and analyzing technical documents and costs from actual projects. The obtained data were analyzed using the Relative Importance Index (RII) method to assess key aspects such as cost efficiency, ease of installation, and material durability. The results showed that HDPE pipes offer superior cost and time efficiency compared to the others. The cost difference between HDPE and uPVC pipes is Rp1,407,577, while that with GI pipes is Rp731,885. In terms of time, HDPE pipes can reduce implementation duration by up to 39 days compared to uPVC pipes and by 9 days compared to GI pipes.